The Application of the Legal Function of the State Attorney to Realize Legal Certainty in Civil and State Administrative Cases - Sasongko, Andy (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Law of the Republic of Indonesia Number 11 of 2021 amending Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia, stipulates the authority of the Prosecutor's Office in the field of Civil and State Administration (DATUN). In this context, the State Attorney (JPN) plays an important role in ensuring legal certainty, justice and expediency in DATUN cases. This article explores the legal function of JPN and its relevance to the study of legal philosophy. This article is based on normative juridical research to show that the JPN has a significant legal function in creating legal certainty in administrative law cases. The JPN's authority is supported by regulations such as the Prosecutor's Law and the Attorney General's Regulation which emphasize the vital role of the Prosecutor's Office in ensuring legal certainty globally, both inside and outside the Court, on behalf of the State or the Government.